2014
DOI: 10.3390/rs6087360
|View full text |Cite
|
Sign up to set email alerts
|

Estimating High Spatial Resolution Air Temperature for Regions with Limited in situ Data Using MODIS Products

Abstract: Abstract:The use of land surface temperature and vertical temperature profile data from Moderate Resolution Imaging Spectroradiometer (MODIS), to estimate high spatial resolution daily and monthly maximum and minimum 2 m above ground level (AGL) air temperatures for regions with limited in situ data was investigated. A diurnal air temperature change model was proposed to consider the differences between the MODIS overpass times and the times of daily maximum and minimum temperatures, resulting in the improveme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…Data from Table 2 illustrates the minimum and maximum differences in values between estimated LSTs and the meteorological air temperatures (MATs) were 1.1-4.2 o C, 0.9-4.0 o C and 0.6-4.0 o C at the three time points, respectively. These positive differences are similar to those reported in previous studies of Chan et al (2018) and Rhee and Im (2014) that the day LST is higher than air temperature. The two main metrics, root mean square error (RMSE) and mean absolute error (MAE), were determined with the values of 2.3 o C and 2.0 o C on 30 September 1996, 2.6 o C and 2.6 o C on 24 May 2007, and 2.2 o C and 1.9 o C on 01 June 2016.…”
Section: Lst In 1996 2007 and 2016supporting
confidence: 92%
“…Data from Table 2 illustrates the minimum and maximum differences in values between estimated LSTs and the meteorological air temperatures (MATs) were 1.1-4.2 o C, 0.9-4.0 o C and 0.6-4.0 o C at the three time points, respectively. These positive differences are similar to those reported in previous studies of Chan et al (2018) and Rhee and Im (2014) that the day LST is higher than air temperature. The two main metrics, root mean square error (RMSE) and mean absolute error (MAE), were determined with the values of 2.3 o C and 2.0 o C on 30 September 1996, 2.6 o C and 2.6 o C on 24 May 2007, and 2.2 o C and 1.9 o C on 01 June 2016.…”
Section: Lst In 1996 2007 and 2016supporting
confidence: 92%
“…The total number is not equal to 52 because two studies were applied for both daily and weekly Ta, 48,123 and one study was applied to estimate both daily and monthly Ta. 124 In addition, the difference between daily, weekly, and monthly articles also suggests that the high temporal resolution of MODIS LST data (four times daily) is one of the largest advantages of MODIS data and is, therefore, widely applied for Ta estimation.…”
Section: Air Surface Temperature Estimation Using Modis Lst Datamentioning
confidence: 99%
“…Mohan et al (2013) assessed the urban heat island intensity in the megacity of Delhi and identified many hot spots of temperature in densely populated areas and commercial regions. Thus, there has been an effort to estimate air temperature using remote sensing to better understand heat island effect (Miliaresis and Tsatsaris 2011;Hill 2013;Rhee and Im 2014).…”
Section: Introductionmentioning
confidence: 99%